The EF-Hand Ca2+ Binding Protein MICU Choreographs Mitochondrial Ca2+ Dynamics in Arabidopsis. Issue 11 (3rd November 2015) - Wagner, Stephan; Behera, Smrutisanjita; De Bortoli, Sara; Logan, David C.; Fuchs, Philippe; Carraretto, Luca; Teardo, Enrico; Cendron, Laura; Nietzel, Thomas; Füßl, Magdalena; Doccula, Fabrizio G.; Navazio, Lorella; et al.
Abstract : The mitochondrial Ca 2+ uptake protein At-MICU shapes mitochondrial Ca 2+ dynamics, providing molecular in vivo evidence for the existence and function of a mitochondrial uniporter complex in plants. Abstract: Plant organelle function must constantly adjust to environmental conditions, which requires dynamic coordination. Ca 2+ signaling may play a central role in this process. Free Ca 2+ dynamics are tightly regulated and differ markedly between the cytosol, plastid stroma, and mitochondrial matrix. The mechanistic basis of compartment-specific Ca 2+ dynamics is poorly understood. Here, we studied the function of At-MICU, an EF-hand protein of Arabidopsis thaliana with homology to constituents of the mitochondrial Ca 2+ uniporter machinery in mammals. MICU binds Ca 2+ and localizes to the mitochondria in Arabidopsis. In vivo imaging of roots expressing a genetically encoded Ca 2+ sensor in the mitochondrial matrix revealed that lack of MICU increased resting concentrations of free Ca 2+ in the matrix. Furthermore, Ca 2+ elevations triggered by auxin and extracellular ATP occurred more rapidly and reached higher maximal concentrations in the mitochondria of micu mutants, whereas cytosolic Ca 2+ signatures remained unchanged. These findings support the idea that a conserved uniporter system, with composition and regulation distinct from the mammalian machinery, mediates mitochondrial Ca 2+ uptake in plants under in vivo conditions. They further suggest that MICU acts as a throttle that controls Ca 2+ uptake by moderating influx, thereby shaping Ca 2+ signatures in the matrix and preserving mitochondrial homeostasis. Our results open the door to genetic dissection of mitochondrial Ca 2+ signaling in plants.